2022
DOI: 10.4274/nkmj.galenos.2021.57966
|View full text |Cite
|
Sign up to set email alerts
|

Does the Pathology Education Received in the Undergraduate Preclinical Years Provide Benefits in the Clinical Education Period? A Survey on 5<sup>th</sup> Grade Medical Students

Abstract: Aim:We aimed to evaluate the perceptions of 5 th grade medical faculty students regarding the adequacy of the pathology education they received in the preclinical period and the benefit of it in clinical clerkship training, Materials and Methods: A 14-question digital questionnaire consisting of open-ended and multiple choice questions was created and sent via e-mail and whatsapp to the students who were in the 3 rd grade at our faculty of medicine in the 2018-2019 academic year and were in the 5 th grade in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Students considered case-based learning and macroscopy training as the most effective methods and suggested that they should be emphasized. It was reported that didactic lessons were more useful when combined with different methods such as case-based learning, assignments/projects, presentation, and microscopy studies ( 51 ). In the second study, a survey was conducted in a heterogeneous group of doctors from different specialties or general practitioners who graduated after 2000, with an objective to explore which method of undergraduate pathology education was most beneficial for their active professional lives.…”
Section: Opinions and Experiences Regarding The Methods Used In Under...mentioning
confidence: 99%
See 2 more Smart Citations
“…Students considered case-based learning and macroscopy training as the most effective methods and suggested that they should be emphasized. It was reported that didactic lessons were more useful when combined with different methods such as case-based learning, assignments/projects, presentation, and microscopy studies ( 51 ). In the second study, a survey was conducted in a heterogeneous group of doctors from different specialties or general practitioners who graduated after 2000, with an objective to explore which method of undergraduate pathology education was most beneficial for their active professional lives.…”
Section: Opinions and Experiences Regarding The Methods Used In Under...mentioning
confidence: 99%
“…The physicians considered the utility of the information (n=89, 83.2%), teaching methods (n=78, 72.9%), and the characteristics of the educator (n=75, 70.1%) to be important. They recommended case discussions (n=79, 72.9%), macroscopy (n=65, 60.7%), microscopy studies (n=62, 57.9%), problem-based learning (PBL) (n=61, 57.0%), and observation in the hospital laboratory (n=51, 47.6%) as major components of pathology education ( 51 ).…”
Section: Opinions and Experiences Regarding The Methods Used In Under...mentioning
confidence: 99%
See 1 more Smart Citation